Analisis Good Corporate Governance Pada Koperasi - Tony Soebijono; Martinus Sony Erstiawan; Lilis Binawati (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2017)
In the 1945 Constitution of the State of the Republic of Indonesia there is a chapter that makes the foundation of the establishment and development of Koperasi in Indonesia. Article 33 of the 1945 Constitution of the State of the Republic of Indonesia states that the economy is constituted as a joint effort based on the principle of kinship. In order for Koperasi to develop properly, it is necessary to have a Good Corporate Governance (GCG). To be able to have good governance, then in managing Koperasi there must be transparency, independence, accountability, responsibility, fairness and equality which are the basic principles in good organizational management. This research will try to observe whether Koperasi has implemented the basic principles of Good Corporate Governance (GCG). The research was conducted at Koperasi Pegawai in Surabaya by using research and development approach and descriptive data analysis. The results of data processing show that the principle of transparency obtained index 3.25 can be implemented well which indicated by financial reporting that has been audited by Public Accounting Firm (KAP) for 8 years. The principle of independence obtained index 3.71 is quite manifest in its management. The principle of accountability with the 3.00 index can be implemented well, as indicated by the presence of AD/ART (Anggaran Dasar/Anggaran Rumah Tangga), vision, mission and purpose of the establishment of Koperasi which all refer to Act Number 25 Year 1992. The rules are implemented and conditioned according to the conditions of the Koperasi. The principle of responsibilitas with index 2.71 also can be done well, with the obedience to the regulation of Act Number 25 Year 1992 which is part of responsibility of management and member of Koperasi in execution of duty. The principle of fairness and equality with the 3.43 index is well executed, there is no discrimination due to differences in ethnicity, religion, race, class, gender and physical condition.